Analisis Kesalahan Peserta Didik Menurut Kastolan dalam Menyelesaikan Soal Literasi Matematika Materi Statistika - Farhana, Atika; Yuanita, Putri; Kartini (Circle: Jurnal Pendidikan Matematika, 2025)
Mathematical literacy is an important skill that every student should possess as it can help students solve problems in everyday life. In fact, field data shows that mathematical literacy is still low based on the 2022 PISA survey results, which revealed that Indonesia only scored 366, far below the OECD average. This study aims to identify the types of errors made by students in solving mathematical literacy problems in statistics material based on Kastolan's theory, namely: (1) conceptual errors, (2) procedural errors, and (3) technical errors. The research conducted is a descriptive qualitative study using data collection techniques including tests and interviews by providing three mathematical literacy test questions to 20 seventh-grade junior high school students. The results obtained based on students' answers show that students made all types of mistakes according to Kastolan's theory in solving mathematical literacy problems in statistics material. The conceptual error rate was 30.4% with a fairly severe category, procedural errors were 34.4% with a fairly severe category, and technical errors were 30.4% with a fairly severe category. This study provides an overview of the mistakes made by students in solving mathematical literacy problems in statistics, allowing for follow-up actions to improve students' mathematical literacy.